Inflammasome Proteins in Serum and Serum-Derived Extracellular Vesicles as Biomarkers of Stroke - Kerr, Nadine; García-Contreras, Marta; Abbassi, Sam; Mejias, Nancy H.; Desousa, Brandon R.; Ricordi, Camillo; Dietrich, W. Dalton; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Molecular Neuroscience, 2018)
The inflammasome is a key contributor to the inflammatory innate immune response after stroke. We have previously shown that inflammasome proteins are released in extracellular vesicles (EV) after brain and spinal cord injury. In addition, we have shown that inflammasome proteins offer great promise as biomarkers of central nervous system injury following brain trauma. In the present study, we used Simple Plex Assay (Protein Simple), a novel multi-analyte automated microfluidic immunoassay platform, to analyze serum and serum-derived EV samples from stroke patients and control subjects for inflammasome protein levels of caspase-1, apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC), Interleukins (IL)-1 and (IL)-18. Receiver operator characteristic (ROC) curves with associated confidence intervals obtained from the analysis of serum samples revealed that the area under the curve (AUC) for ASC was 0.99 with a confidence interval between 0.9914 to 1.004, whereas the AUC for caspase-1, IL-1 and IL-18 were 0.75, 0.61 and 0.67, respectively. Thus, these data indicate that ASC is a reliable biomarker of stroke and highlight the importance of the inflammasome in the inflammatory response after brain ischemia.